Influences of Therapeutic Communication on Model of Structural Reflection on Parents of Patients Satisfaction - Agostinha Soares; Kusnanto Kusnanto; Ninuk Dian Kurniawati (Faculty of Nursing, Universitas Jember, 2020)
Therapeutic communication with reflection is a process of learning from experience, recapturing practical experience and reflecting on it critically to gain new understanding, tends to involve individual practitioners to become self-aware of the situation. However, at the Hospital in Dili Timor Leste the nurse does not explain the procedure of giving medication to the patient's parents. The general purpose of the study is to know the effect of therapeutic communication with the model of structural reflection on patient parent satisfaction. In this study using a posttest-only control group design with a sample of 126 people in each group of 63 people Purposive sampling method. Intervention using the MSR module, for 3 consecutive days, on the third day the two groups conducted a post-test using a questionnaire on patient satisfaction, using Mann Whitney analysis.The results of this study obtained a value of p = 0,000 which means that there is a significant influence between the control group in the perinatology room and the intervention group in the pediatric room on the satisfaction of patients' parents in the Pediatric Department of Hospital Dili Timor Leste. Therapeutic communication with the structural reflection model (MSR) has a positive influence on the patient's parents at the Dili Timor Teste Hospital, the patient's parents are very satisfied with the communication made by the nurse, with therapeutic communication the nurse looks for the patient, supports, supports, questions, establishes a relationship of trust , the method required by this MSR needs to be applied in Hospital Dili Timor Leste